2021
DOI: 10.1186/s13690-021-00745-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among Syrian refugees in Germany: a cross-sectional pilot study

Abstract: Background More than 10 million Syrians have left their homes and sought refuge in neighboring countries, including Europe, since the beginning of the Syrian conflict in March 2011, and immigration continues to this day. This cross-sectional study included Syrian refugees residing in and around Hannover, Germany. We investigated whether general socioeconomic factors (e.g. age, sex, housing, asylum duration) were predictive factors for the quality of life (QOL) of Syrian refugees in Germany. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…There may be many stressful life events like adverse life conditions, problems in feeding, housing, and education in refugee children’s lives, and traumatic experiences (Kandemir et al, 2018 ). These adversities may cause impairment in refugees’ life quality (Abdo et al, 2019 ; Al Masri et al, 2021 ; Leiler et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There may be many stressful life events like adverse life conditions, problems in feeding, housing, and education in refugee children’s lives, and traumatic experiences (Kandemir et al, 2018 ). These adversities may cause impairment in refugees’ life quality (Abdo et al, 2019 ; Al Masri et al, 2021 ; Leiler et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…There may be many stressful life events like adverse life conditions, problems in feeding, housing, and education in refugee children’s lives, and traumatic experiences (Kandemir et al, 2018 ). These adversities may cause impairment in refugees’ life quality (Abdo et al, 2019 ; Al Masri et al, 2021 ; Leiler et al, 2019 ). Additionally, there are some difficulties caused by Covid 19 pandemic in this period, and it was reported that individuals' mental health problems and support need to be increased during the COVID-19 pandemic period ( (Ferreira et al, 2021 ; Suryavanshi et al, 2020 ; Riiser et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations